Use of ablation-season albedo as an indicator of annual mass balance of four glaciers in the Tien Shan - Yue, Xiaoying; Li, Zhongqin; Wang, Feiteng; Li, Huilin (Frontiers in Earth Science, 2023)
Glacier mass balance and its sensitivity to climate change depend to a large degree on the albedo and albedo feedback. Although recent increasing studies reconstruct the annual surface mass balance (SMB) based on the relationships between satellite-derived minimum albedo and annual glaciological mass balance (so-called albedo method), a relationship remains conjectural for Tien Shan glaciers. Accumulation and ablation occur simultaneously in summer, causing different surface processes. We examine this relationship using glaciological mass-balance data and the equilibrium-line altitude (ELA) made on the eastern branch of Urumqi Glacier No. 1 (UG1-E), Tuyuksu, Golubin and Glacier No. 354, and ablation-season (May–September) albedo retrieved from Moderate Resolution Imaging Spectroradiometer (MODIS) images from 2000 to 2021. Compared with minimum ablation-season albedo, we find higher coefficients of determination between mean ablation-season albedo and glaciological mass balance at UG1-E and Tuyuksu. In contrast, for Golubin and Glacier No. 354, glaciological mass balance is higher correlated to minimum ablation-season albedo than mean ablation-season albedo. This difference is related to the glaciological mass-balance time period. The relationship between albedo and glaciological mass balance is obtained over a shorter time for Golubin (8 years) and Glacier No. 354 (9 years) than for UG1-E (20 years) and Tuyuksu (20 years). Nonetheless, based on the correlativity between MODIS-derived mean ablation-season albedo and minimum ablation-season albedo and glaciological mass balance of Golubin and Glacier No. 354 over the 2011–2019 period, the annual SMB for these glaciers can be reconstructed using the albedo method over the period 2000–2010. Comparison with previously reconstructed results indicated that the mass balance derived from albedo is robust for Glacier No. 354, while for Golubin, the results derived from the albedo method only captured the relative changes in mass balance. The current study suggested that ablation-season albedo can be regarded as a proxy for annual mass balance, and mean ablation-season albedo may be more reliable than minimum ablation-season albedo for some Tien Shan glaciers.